2020
DOI: 10.1097/md.0000000000018793
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between body mass index and arterial stiffness in a health assessment Chinese population

Abstract: Pulse wave velocity (PWV) is a reliable measurement of arterial stiffness. Our study assesses the association between body mass index (BMI) and brachial-ankle PWV (baPWV) in a healthy cohort and seeks to explain possible mechanisms associated with the obesity paradox. A cross-sectional study was conducted in 578 normal individuals. The mean age was 48.3 ± 14.6 years, and 468 (81.0%) were men. 288 subjects (49.8%) were overweight and obese. baPWV and ankle-brachial index (ABI) were performed to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 30 publications
6
31
0
1
Order By: Relevance
“…Their results showed that patients with lower admission MAP (<79 mmHg) presented worse inhospital prognosis (15). Interestingly, obesity (BMI ≥ 25 kg/m 2 ) was significantly related to higher average SBP, DBP, and MAP (16,25,26). These observations indicated an inhibitive role of obesity in the progression of MI.…”
Section: Discussionmentioning
confidence: 98%
“…Their results showed that patients with lower admission MAP (<79 mmHg) presented worse inhospital prognosis (15). Interestingly, obesity (BMI ≥ 25 kg/m 2 ) was significantly related to higher average SBP, DBP, and MAP (16,25,26). These observations indicated an inhibitive role of obesity in the progression of MI.…”
Section: Discussionmentioning
confidence: 98%
“…The data on the association between BMI and arterial stiffness parameters is, on the other hand, contradictory. In a study by Tang et al, the authors found a significant increase in ankle-brachial pulse wave velocity (abPWV) in patients with higher BMI values in studied cohort [ 40 ], while Rodriques et al failed to prove an independent association between cfPWV and BMI [ 41 ]. The authors Desamericq et al performed a study on 2.034 patients in which they found no relationship between cfPWV and BMI as well [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…7) The possible mechanism underlying the differential effect of shortterm exposure to PM10 on high PWV in non-obese subjects may be as follows. Previously, Tang et al 20) suggested that obese individuals have greater nutritional reserves and can therefore cope better with acute stressful events and increased metabolic demands due to the benefi- sure and underestimate the association in long-term exposure-related adverse health effects. Finally, because we did not have information regarding the timing of the activities of each patient, we could not ascertain the exact location and timing of exposure to PM10, which could lead to a bias if the PM10 levels between the patient's workplace and residence differ.…”
Section: Discussionmentioning
confidence: 99%
“…The possible mechanism underlying the differential effect of short-term exposure to PM 10 on high PWV in non-obese subjects may be as follows. Previously, Tang et al [ 20 ] suggested that obese individuals have greater nutritional reserves and can therefore cope better with acute stressful events and increased metabolic demands due to the beneficial effect of adipose tissue induced by beneficial hormones and cytokines. In our study, relatively healthy, non-obese individuals showed significantly lower body fat percentage based on our data (body fat % of obese versus non-obese=30.4% versus 25.9%), which may be a possible mechanism by which non-obese individuals have difficulty coping with short-term exposure to PM 10 , resulting in high PWV.…”
Section: Discussionmentioning
confidence: 99%